Photoacoustic microscopy imaging for microneedle drug delivery - Moothanchery, Mohesh (2018)
The recent development of novel transdermal drug delivery systems (TDDS) using microneedle technology allows micron-sized conduits to be formed within the outermost skin layers attracting keen interest in skin as an interface for localized and systemic delivery of therapeutics. In light of this, researchers are using microneedles as tools to deliver nanoparticle formulations to targeted sites for effective therapy. However, in such studies the use of traditional histological methods are employed for characterization and do not allow for the in vivo visualization of drug delivery mechanism. Hence, this study presents a novel imaging technology to characterize microneedle based nanoparticle delivery systems using optical resolution-photoacoustic microscopy (OR-PAM). In this study in vivo transdermal delivery of gold nanoparticles using microneedles in mice ear and the spatial distribution of the nanoparticles in the tissue was successfully illustrated. Characterization of parameters that are relevant in drug delivery studies such as penetration depth, efficiency of delivered gold nanoparticles were monitored using the system. Photoacoustic microscopy proves an ideal tool for the characterization studies of microneedle properties and the studies shows microneedles as an ideal tool for precise and controlled drug delivery.